2021
DOI: 10.35882/jeeemi.v3i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Dual SpO2 Monitoring in Premature Babies Via Bluetooth Communication

Abstract: Monitoring the baby's health status is very important, especially for babies born prematurely. Oxygen saturation levels in newborns are very important to know because when the oxygen saturation levels in newborns are low, it is necessary to watch out for hemodynamic abnormalities in the baby. Measurement of oxygen saturation levels in newborns can help detect congenital abnormalities in infants early. This study aims to design an equipment system to continuously monitor the condition of oxygen saturation in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Based on M. Syahrul Azam [25], the results of his research obtained the error value of the highest SpO2 sensor of 0.68% and the smallest 0.17%. While other similar studies stated the error value in the range of 0.0123% [26], 1% [27], >3% [28], 0.38% [29], 0.81% [30], 1% [31], and other study revealed deviation value approximately 1.62% [32].…”
Section: Discussionmentioning
confidence: 79%
“…Based on M. Syahrul Azam [25], the results of his research obtained the error value of the highest SpO2 sensor of 0.68% and the smallest 0.17%. While other similar studies stated the error value in the range of 0.0123% [26], 1% [27], >3% [28], 0.38% [29], 0.81% [30], 1% [31], and other study revealed deviation value approximately 1.62% [32].…”
Section: Discussionmentioning
confidence: 79%
“…Births that occur between 38 and 40 weeks of pregnancy and with babies weighing between 2500 and 4000 grams are considered full-term [1][2][3][4] [5]. Premature birth is a risk factor for infant mortality [6]because to the vulnerability of premature babies' bodies to harm and their immature organ systems such the lungs, heart, kidneys, liver, and digestive tract [7] [8]. Therefore, further precautions must be taken, such as recreating the conditions of the womb in terms of temperature, humidity, and oxygen levels.…”
Section: Introductionmentioning
confidence: 99%
“…Then the last one was developed by Azkiyak et al and other studies; this device is already portable using an Android display and is equipped with storage. However, there are still shortcomings, namely errors that still exceed 5% [13]- [17]. The biggest error on the DS18B20 sensor is 4.33325%, while the biggest error on the K-type Thermocouple temperature sensor is 7.3138%.…”
Section: Introductionmentioning
confidence: 99%